Transformasi Sistem Produksi Tanaman Pangan Menjadi Tanaman Tahunan di Lahan Kering: Ancaman bagi Keamanan Pangan - Sudaryono, Sudaryono; Hastuti, P. C. (Iptek Tanaman Pangan, 2011)
Transformation of annual to perennial crop production system in sub optimal dry land. Agricultural land resources as media for annual-perennial crops production system are the main backbone of the biological industry. Proportion and management of annual-perennial crops to be part of integrated system can not be separated in the system of food crop production supply. All crop products are useful to consumers and market segments. In other word, all harvested produces have economic values. In a high productive farm lands with small erosion and less land degradation, the sustainability of such land is maintained. However, on sub-optimum dry lands the degree of erosion tends to be higher and land degradation accours rapidly, if it is not properly managed. Intensive crop rotation of annual crops may result in nutrient depletion, soil erosion and unsustainability of crop production. Planting perennial crop in a mixture with annual crop produces better canopy coverage to the soil surface which leads to the reducing of soil erosion, and hence, better soil conservation for sustainable production. The proper portion of perennial to annual crops on such land should be considered, so as to maintain the sufficient food crop production for the people in the area. Thus, farm management on a fragile lands should considered both food sufficiency and production sustainability.